2014
DOI: 10.1055/s-0033-1341236
|View full text |Cite
|
Sign up to set email alerts
|

A Short Synthesis of Partially Protected l- and d-β-Hydroxyenduracididines and a Structurally Simplified Dipeptide Analogue

Abstract: A short synthesis of the C2-epimeric amino acids Land D-β-hydroxyenduracididine (βhEnd) was developed. Both amino acids are part of the cyclopeptide portion of the mannopeptimycin antibiotics. The synthetic route comprises eight steps starting from Garner's aldehyde and provides partially protected derivatives in good overall yields. Key steps are a stereodivergent olefinationbishydroxylation sequence and a regioselective guanidine cyclization reaction. In addition, precursor amino acids that contain a protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Synthesis of β-hydroxyenduracididine by Oberthür et al: In 2014, Oberthür et al reported a second generation synthesis of β-hydroxyenduracididine using a more concise route to orthogonally protected amino acids 46 and 47 (Scheme 7) [58]. Installation of the C-2 stereocentre again began with Garner’s aldehyde 48 and Wittig olefination, followed by Sharpless dihydroxylation to stereoselectively afford diol 49 [5960].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of β-hydroxyenduracididine by Oberthür et al: In 2014, Oberthür et al reported a second generation synthesis of β-hydroxyenduracididine using a more concise route to orthogonally protected amino acids 46 and 47 (Scheme 7) [58]. Installation of the C-2 stereocentre again began with Garner’s aldehyde 48 and Wittig olefination, followed by Sharpless dihydroxylation to stereoselectively afford diol 49 [5960].…”
Section: Reviewmentioning
confidence: 99%
“…An alternative route to L-β-hydroxyenduracididine based on the synthesis reported by Oberthür et al [58] afforded L-β-hydroxyenduracididine 98 in 7% yield over twelve steps from 99 (Scheme 20). …”
Section: Reviewmentioning
confidence: 99%